2002
DOI: 10.1093/aob/mcf103
|View full text |Cite
|
Sign up to set email alerts
|

Rubisco Activity: Effects of Drought Stress

Abstract: Ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco) activity is modulated in vivo either by reaction with CO2 and Mg2+ to carbamylate a lysine residue in the catalytic site, or by the binding of inhibitors within the catalytic site. Binding of inhibitors blocks either activity or the carbamylation of the lysine residue that is essential for activity. At night, in many species, 2-carboxyarabinitol-1-phosphate (CA1P) is formed which binds tightly to Rubisco, inhibiting catalytic activity. Recent work has s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
235
1
15

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 409 publications
(264 citation statements)
references
References 40 publications
13
235
1
15
Order By: Relevance
“…A fluorescência da clorofila é considerada uma ferramenta para determinação de estresse em plantas, pois indica que a energia da radiação solar não está sendo utilizada de forma eficiente (MAXWELL & (BERTOLLI et al, 2012). Ainda, a recuperação limitada da taxa de fotossíntese líquida em soja, submetida à indução lenta e rápida de déficit hídrico, após reidratação, provavelmente, foi causada por fatores bioquímicos (BERTOLLI et al, 2012), tais como decréscimo na síntese de RuBP (BOTA et al, 2004) e na atividade da Rubisco (PARRY et al, 2002).…”
Section: Resultsunclassified
“…A fluorescência da clorofila é considerada uma ferramenta para determinação de estresse em plantas, pois indica que a energia da radiação solar não está sendo utilizada de forma eficiente (MAXWELL & (BERTOLLI et al, 2012). Ainda, a recuperação limitada da taxa de fotossíntese líquida em soja, submetida à indução lenta e rápida de déficit hídrico, após reidratação, provavelmente, foi causada por fatores bioquímicos (BERTOLLI et al, 2012), tais como decréscimo na síntese de RuBP (BOTA et al, 2004) e na atividade da Rubisco (PARRY et al, 2002).…”
Section: Resultsunclassified
“…It is well-known that drought can cause the decrease on synthesis of rubisco (Vu et al 1999) and a loss of rubisco activity (Parry et al 2002;Chaitanya et al 2003), and the decline in the rubisco activity is mainly due to the proteolysis of the large subunit (Hajheidari et al 2005;Jorge et al 2006). However, in agreement with our findings, Rizhsky et al (2002) reported that drought greatly increases the number of transcripts encoding the large subunit of rubisco in tobacco and suggested that the large subunit of rubisco, as a protein of the PSI reaction center, may take part in the cyclic electron flow pathway through which some energy can dissipate during stress (Rizhsky et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…During WD, the reduction of photosynthesis has been attributed to reduction of Rubisco activity due to a decrease of Rubisco activase, the energy component of photosynthesis, RuBP regeneration, and severe conditions in the chloroplasts and reactive oxygen species (ROS) generation under limited supply of CO 2 (Lawlor & Tezara 2009). Rubisco activity reduction has generally been found under severe WD (Maroco et al 2002;Parry et al 2002;Flexas et al 2006). Alterations in both stomatal and non-stomatal limitations have been shown during WD periods and rewatering (Costa Franca et al 2000;Singer et al 2003;Efeoglu et al 2009).…”
Section: Research Article Leaf Recovery Responses During Rehydrationmentioning
confidence: 99%